2007
DOI: 10.1097/01.pcc.0000262798.84416.c5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parental presence during bedside pediatric intensive care unit rounds: Effect on duration, teaching, and privacy*

Abstract: Parental presence on rounds does not seem to interfere with the educational and communication process. Parents report satisfaction with participation in rounds, and privacy violations do not seem to be a concern from their perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 13 publications
4
53
0
Order By: Relevance
“…Our findings are more consistent with those of Kuo et al, 13 who reported that family participation during rounds was associated with higher parental satisfaction, improved and consistent transfer of medical information, discussion of care plan, and participation in decision making; and Phipps et al, 10 who reported that parental presence during rounds did not inhibit teaching. Our study also supports the finding of others that parental participation minimizes parental anxiety, builds trust, and improves communication and team building between the family and the medical team.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are more consistent with those of Kuo et al, 13 who reported that family participation during rounds was associated with higher parental satisfaction, improved and consistent transfer of medical information, discussion of care plan, and participation in decision making; and Phipps et al, 10 who reported that parental presence during rounds did not inhibit teaching. Our study also supports the finding of others that parental participation minimizes parental anxiety, builds trust, and improves communication and team building between the family and the medical team.…”
Section: Discussionsupporting
confidence: 83%
“…The initial concerns voiced by our CTICU staff, as well as in published reports, regarding privacy issues, increasing parental anxiety, increasing duration of rounds, decreasing teaching during rounds, and concerns for parents' understanding of complex discussions [8][9][10][11] were not found to be true in our experience. Our findings are more consistent with those of Kuo et al, 13 who reported that family participation during rounds was associated with higher parental satisfaction, improved and consistent transfer of medical information, discussion of care plan, and participation in decision making; and Phipps et al, 10 who reported that parental presence during rounds did not inhibit teaching.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…36 | VOLUME 16 and is consistent with a study of work rounds on a general internal medicine unit. 23 However, the range of our recorded rounding times is striking.…”
Section: An Official Journal Of the American Academy Of Pediatricssupporting
confidence: 60%
“…There are also concerns that rounds may not be the best avenue to convey information and solicit family input in decision making. Conversely, there is a fear that the presence of parents might inhibit open discussion among staff [51,52].…”
Section: Family-centered Carementioning
confidence: 91%